Efektivitas Penyaluran Dana Desa Pada Bidang Peternakan dan Pertanian di Desa Rumoong Atas Dua, Tareran Berdasarkan UU Nomor 6 Tahun 2014 - Mesra, Romi; Wereh, Agustien Cherly; Kasenda, Marven A.; Sidayang, Stience (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to determine how effective the distribution of village funds in the field of animal husbandry and agriculture is in the village of Rumoong Atas Dua and to determine the impact of the effectiveness of the distribution of village funds. This research was conducted in the village of Rumoong on two, while the method used was qualitative research by collecting observation data, direct interviews with several informants. The results of the research generally show that the program for distributing funds in the field of animal husbandry and agriculture is a program that really helps the family economy in the village of Rumoong Atas Dua. but in carrying out this livestock and agriculture program, the government must also spend village funds to make road access to livestock and agriculture locations. with that the community also intervenes or works together in making roads to livestock and agriculture locations..